Large-Scale Yielding Failure Prediction of Notched Ductile Plates by Means of the Linear Elastic Notch Fracture Mechanics - Torabi, A.R.; Campagnolo, A.; Berto, F. (Проблемы прочности, 2017)
The main goal of this research is to propose a failure criterion based on the linear elastic notch fracture mechanics (LENFM) for predicting tensile crack initiation from a blunt V-notch, encountering large plasticity at the notch vicinity. First, some most recently published experimental results on tensile failure of V-notched ductile aluminum plates are briefly described. Then, with the aim to avoid complex and time-consuming elastic-plastic analyses, the equivalent material concept (EMC) is employed together with a LENFM-based fracture criterion, namely the averaged strain energy density (ASED) criterion, for predicting the load-carrying capacity of the V-notched aluminum plates. A very good agreement is shown to exist between the experimental results and theoretical predictions of the EMC-ASED criterion. Предложен критерий разрушения, основанный на линейной упругой механике разрушения, для прогнозирования инициирования трещины растяжения от затупленного V-образного надреза при большой пластичности вблизи надреза. Описаны некоторые современные экспериментальные результаты по разрушению при растяжении пластичных алюминиевых пластин с V-образным надрезом. С целью избежания сложного и трудоемкого упругопластического анализа для прогнозирования несущей способности алюминиевых пластин с V-образным надрезом используются концепция эквивалентного материала и критерий усредненной плотности энергии деформации, базирующийся на линейной упругой механике разрушения. Показано хорошее соответствие между экспериментальными данными и результатами прогнозирования на основе концепции эквивалентного материала и критерия усредненной плотности энергии деформации. Запропоновано критерій руйнування, що базується на лінійній пружній механіці руйнування, для прогнозування ініціювання тріщини розтягу від затупленого V-подібного надрізу при значній пластичності поблизу надрізу. Описано деякі сучасні експериментальні результати щодо руйнування при розтязі пластичних алюмінієвих пластин із V-подібним надрізом. Із метою запобігання складного і трудомісткого аналізу для прогнозування несівної здатності алюмінієвих пластин із V-подібним надрізом використовуються концепція еквівалентного матеріалу і критерій усереднено ї щільності енергії деформації, що базується на лінійній пружній механіці руйнування. Показано хороший збіг експериментальних даних із результатами прогнозування на основі концепції еквівалентного матеріалу і критерію усередненої щільності енергії деформації.